1987
DOI: 10.1111/j.1399-3054.1987.tb06139.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among pure cultured strains of Frankia based on host specificity

Abstract: Fifty strains of Frankia were tested for their ability to nodulate six species of actinorhizal plants. Pure cultured strains were used to inoculate seedlings of Alnus glutinosa (L.) Gaertn., Alnus rubra Bong., Casuarina equisetifolia L., Elaeagnus angustifolia L., Hippophaë rhamnoides L. and Myrica cerifera L. in nutrient solution culture. From the results of this study, host inoculation groups among the actinorhizal plants were defined. Although overlap between host inoculation groups appears to be common, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(83 citation statements)
references
References 8 publications
5
78
0
Order By: Relevance
“…Among the isolated strains tested, strain Mg15 isolated from M. gale was found to group with Elaeagnaceae strains by PCR-RFLP but not with the complete rrs gene sequence. However, this strain is atypical, since no nodulation was obtained on its original host plant, M. gale, but was obtained on Elaeagnaceae species (3,31). Thus it can be concluded that even if Myrica is often considered a promiscuous actinorhizal genus, our results show that M. gale does not exhibit such promiscuity in its natural environment.…”
Section: Vol 67 2001mentioning
confidence: 48%
“…Among the isolated strains tested, strain Mg15 isolated from M. gale was found to group with Elaeagnaceae strains by PCR-RFLP but not with the complete rrs gene sequence. However, this strain is atypical, since no nodulation was obtained on its original host plant, M. gale, but was obtained on Elaeagnaceae species (3,31). Thus it can be concluded that even if Myrica is often considered a promiscuous actinorhizal genus, our results show that M. gale does not exhibit such promiscuity in its natural environment.…”
Section: Vol 67 2001mentioning
confidence: 48%
“…Among actinorhizal plants, the family Myricaceae is a good experimental model to study the specificity of symbiotic interactions, as it includes species with either narrow or broad symbiont specificity. Most Myricaceae species are promiscuous (nonselective for Frankia strains), but Myrica gale exhibits a narrow symbiont specificity, being nodulated only by cluster 1a strains (5,27). In addition, M. gale has the novel trait of exuding droplets of secondary metabolites at the fruit surface, and the phenolic contents of these metabolites are significantly different from those of other broad symbiont specificity Myricaceae species (our unpublished data).…”
mentioning
confidence: 99%
“…Moreover, this grouping based on ARDRA is driven by host plant infectivity rather than host plant origin of isolation. Some Casuarina (NRRL-B16306 and NRRL-B16412) and Ceanothus (NRRL-B16316) strains that are non infective on the latter host plant but infective on Elaeagnus (Baker, 1987) (example Casuarina strains) indicate noteworthy genome variability among Frankia strains. While grouping is possible at high cutoff, the generated genogroups are not correlated to host infection groups that are determined in this study based on amplified ribosomal DNA restriction analysis.…”
Section: Resultsmentioning
confidence: 99%